NOTAS SOBRE LA FLORA FOSIL DE LA ZONA DE TICO, PROVINCIA DE SANTA CRUZ 3. Ruflorinia 1Jilifem n. sp. 4. Equisetites sp. (Ameghiniana, 2013)
Several fragmentary fernlike fronds, found in the Ticoa magnipinnulata bed of the Tico Amphitheatre are referred to a new species of Ruflol'inia. A generic diagnosis based on the two species known so far, is established. 4. Equisetites sp. A few fragments of a small plant are referred to the genus· Equise- tites. They have been found in the Tico Amphitheatre in a reduced lenticular bed where this plant is dominant: The lack of sufficient diagnostic characters allows no specific deter- mhiation. This is the first record of a Sphenopsid in the flora of the Baquero Formation.